Evaluation of the Apical Sealing Ability of Bioceramic and AH Plus Root Canal Sealers – An In Vitro Study - Rizvi, Ramla; Khuhawar, Saleem Raza; Sahito , Ashique Hussain; Tagar , Muhammad Rafique; Rafique , Sumaira; Rasheed, Wasfa (Journal of Liaquat University of Medical & Health Sciences, 2021)
OBJECTIVE: Evaluation of apical sealing ability of Bioceramic and AH plus root canal sealers, an in-vitro study. METHODOLOGY: This in vitro non-probability convenient sampling study was conducted at the Department of Operative Dentistry, Liaquat University of Medical and Health Sciences, Jamshoro from June-December 2018. Fresh extracted 32 teeth were included and their crowns were sectioned at Cemento-Enamel Junction/service to obtain 12mm standard root length. The access cavity was gained using endodontic instruments. The teeth were divided into two groups, in Group A (n=16) MTA Bioceramic and in Group B (n=16) AH Plus was used as root canal sealers by single cone obturation technique. The obturated specimens were stored in humid conditions for one week. Analysis was done using SPSS version 20. RESULTS: Mean and standard deviation of dye leakage for Bioceramic were 2.25±0.9 whereas for AH Plus was significantly lower, 1.19±0.75. Teeth included in Group A were central incisors 37.5%, lateral incisors 18.8%, canine 12.5%, lower first premolars 12.5% and second premolars 6.3%, whereas Group B consisted of central incisors 18.8%, lateral incisors 12.5 %, canine 12.5%, lower first premolars 18.8 % and second premolars 6.3%. Dye leakage was higher in Group A compared to Group B with a significant P-value < 0.001. CONCLUSION: It can be concluded based on this study that AH Plus offers a better apical seal as compared to Bioceramic-based MTA Fillapex sealers. KEYWORDS: Methylene Blue, Dye, Microleakage, Bioceramic, Apical Seal, Root Canal Sealers, Obturation, MTA, AH plus